Cellular Mechanisms of FGF-Stimulated Tissue Repair - Igor Prudovsky (Cells, 2021)
Growth factors belonging to the FGF family play important roles in tissue and organ repair after trauma. In this review, I discuss the regulation by FGFs of the aspects of cellular behavior important for reparative processes. In particular, I focus on the FGF-dependent regulation of cell proliferation, cell stemness, de-differentiation, inflammation, angiogenesis, cell senescence, cell death, and the production of proteases. In addition, I review the available literature on the enhancement of FGF expression and secretion in damaged tissues resulting in the increased FGF supply required for tissue repair.